2021
DOI: 10.4018/jgim.20211101.oa43
|View full text |Cite
|
Sign up to set email alerts
|

CEO Exposure, Media Influence, and Stock Returns

Abstract: Media-aware stock movements are well acknowledged by the behavioral finance. As the soul of a firm, CEO’s media behavior is critical to the operation of a firm. CEO’s exposure could have captured the investors’ attention and enhanced the media effect in the stock market in terms of the “eyeball economics”, or CEO’s overexposure could have attracted more attention than firm-specific news, which attenuate the media effect in the stock market due to the investors’ limited attention. This study systematically expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Prior studies indicate that the media plays a vital price discovery role in the stock market by exposing key information or affecting investor sentiment (Chan, 2003;Fang & Peress, 2009;Tetlock, 2007;Chen et al, 2021). Due to technical limitations, media influence is represented as a Boolean or numeric value in the pilot research.…”
Section: Media Platformsmentioning
confidence: 99%
“…Prior studies indicate that the media plays a vital price discovery role in the stock market by exposing key information or affecting investor sentiment (Chan, 2003;Fang & Peress, 2009;Tetlock, 2007;Chen et al, 2021). Due to technical limitations, media influence is represented as a Boolean or numeric value in the pilot research.…”
Section: Media Platformsmentioning
confidence: 99%
“…As such, the impact of news is derived from investors' attention to its content (Li et al, 2018). Limited attention theory posits that the impact of different information on investors' attention varies (Chen et al, 2021). For example, Li et al (2014b) found that news on topics such as penalties for violations, mergers, and acquisitions had a greater impact on the stock market than on topics such as executive and operational performance.…”
Section: Related Workmentioning
confidence: 99%
“…The most common research uses content to predict the performance of stock markets. In fact, in recent years, research has burgeoned surrounding social media platforms and stock markets (Chen et al, 2021;Jin et al, 2022). While most studies have focused on the wisdom of the crowd (Bollen et al, 2011;Cheng & Yang, 2022), few have concentrated on individual perspectives (Ajjoub et al, 2020).…”
Section: Introductionmentioning
confidence: 99%